An overview of duplex stainless steel for strain induced martensite transformation. (2020) - Koppula, Shivani; Gugulothu, Pallavi; Chilikuri, Akhila; Narum, Snigdha; Subbiah, Ram; Singh, S.K.
Abstract: A study of the deformation behavior of lean duplex stainless steels with martensitic transformation caused by strain is presented. The research is dedicated to investigating a duplex stainless steel's load response. The early grades were chromium, nickel, and molybdenum alloys. Duplex stainless steels, due to their excellent corrosion properties, have many end uses in oil and gas. These were used in subsea applications including flowlines, umbilical tubing, subsea manifolds, lines for water injection and tubing for downhole chemical injection. The strength and ductility of duplex stainless steels is lacking. The distribution of strain-induced martensite (SIM) over a wide range of strain is to be accomplished in order to improve these mechanical properties. The transformation of the martensite induced by the strain is based on optimizing austenite stability. The best combination of strength and ductility, therefore, is achieved.